Agricultural productivity under taungya and non-taungya land-use options: a case study of Vandeikya Local Government area, Benue State, Nigeria (2011)
Taungya farming is a special arrangement between the forestry department and farmers, which combines the production of both arable and forest tree crops simultaneously on a piece of land. The practice was adopted in Vandeikya Local Government area of Benue State Nigeria, in mid 1950s up to 2000. This study evaluated the method as an option for food and fiber production compared to the traditional farming and forest management practices. Using Stratified random sampling, two sets of questionnaire were used to appraise the productivity of some arable crops and forest regeneration under taungya and non-taungya cultural practices. The yields of arable crops were significantly higher under taungya farming that in non-taungya plots in the study area. There was however no significant difference in the total forest area regenerated under the two landuse systems. The apparent land hunger among farmers is a favourable factor for adoption of taungya as a land use option in the study area. There is need to adopt multi-species planting approach in future programmes. Also, the land tenure system which limits access to land by strangers needs to be reviewed and greaterawareness on the programme needs to be generated among the farmers and forestry staff alike.